PENGEMBANGAN MODUL PEMBELAJARAN SAINS BERBASIS INTEGRASI ISLAM-SAINS UNTUK PESERTA DIDIK DIFABEL NETRA MI/SD KELAS 5 SEMESTER 2 MATERI POKOK BUMI DAN ALAM SEMESTA - Husnul Fathonah Wiyandari; Jamil Suprihatiningrum (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2015)
The aims of this research are: 1) to develop science Braille module for blind student at public/Islamic elementary school; 2) to validate science Braille module for blind student at public/Islamic elementary school based on teachers’ assessment. The development of the module followed the 4-D model of the research based development, i.e. Define, Design, Development, and Disseminate. However, the present paper will only report the first three phases that have been conducted. The prototype of the science Braille module was reviewed by supervisor, subject expertise, and peer reviewers. The final prototype of module was reviewed by SLB teacher, elementary school teachers (2 teachers from inclusive school and 1 teacher from SLB) using the manual ideal criteria assessment. The result of this study shows that the prototype of the science Braille module was given a good score by the media expert and the teachers. This module has 7.13% as ideal percentage. Based on the result, the prototype of science Braille module can be used as learning science media, especially for blind students.